Pharmacogenomics and Efficacy of Risperidone Long‐Term Treatment in Thai Autistic Children and Adolescents. Issue 4 (19th June 2017) - Nuntamool, Nopphadol; Ngamsamut, Nattawat; Vanwong, Natchaya; Puangpetch, Apichaya; Chamnanphon, Monpat; Hongkaew, Yaowaluck; Limsila, Penkhae; Suthisisang, Chuthamanee; Wilffert, Bob; Sukasem, Chonlaphat
Abstract: The purpose of this study was to evaluate the association of pharmacogenomic factors and clinical outcome in autistic children and adolescents who were treated with risperidone for long periods. Eighty‐two autistic subjects diagnosed with DSM‐IV and who were treated with risperidone for more than 1 year were recruited. Pharmacogenomics and clinical outcome (CGI‐I, aggressive, overactivity and repetitive score) were evaluated. Almost all patients showed stable symptoms on aggressive behaviour (89.02%), overactivity (71.95%), repetitive (70.89%) behaviour and all clinical symptoms (81.71%). Only 4.48% of patients showed minimally worse CGI‐I score. Patients in the non‐stable symptom group had DRD2 Taq1A non‐wild‐type (TT and CT) frequencies higher than the clinically stable group ( p  =   0.04), whereas other gene polymorphisms showed no significant association. Haplotype ACCTCAT (rs6311, rs1045642, rs1128503, rs1800497, rs4436578, rs1799978, rs6280) showed a significant association with non‐stable clinical outcome (χ 2  = 6.642, p =  0.010). Risperidone levels showed no association with any clinical outcome. On the other hand, risperidone dose, 9‐OH risperidone levels and prolactin levels were significantly higher in the non‐stable compared to the stable symptom group ( p  =   0.013, p  =   0.044, p  =   0.030). Increased appetite was the most common adverse drug reaction and associated with higher body‐weight, whereas it was not significantly associated with genetic variations and non‐genetic information. In conclusion, risperidone showed efficacy to control autism, especially aggressive symptoms in long‐term treatment. However, Taq1A T – carrier of dopamine 2 receptor gene – is associated with non‐stable response in risperidone‐treated patients. This study supports pharmacogenomics testing for personalized therapy with risperidone in autistic children and adolescents.